2000
DOI: 10.4049/jimmunol.165.8.4346
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of p18INK4 and p27kip1 Cyclin-Dependent Kinase Inhibitors Is Regulated Differently During Human B Cell Differentiation

Abstract: Cell cycle progression is under the control of cyclin-dependent kinases (cdks), the activity of which is dependent on the expression of specific cdk inhibitors. In this paper we report that the two cdk inhibitors, p27Kip1 and p18INK4c, are differently expressed and control different steps of human B lymphocyte activation. Resting B cells contain large amounts of p27Kip1 and no p18INK4c. In vitro stimulation by Staphylococcus aureus Cowan 1 strain or CD40 ligand associated with IL-10 and IL-2 induces a rapid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…We show that inhibition of IL-10 results in the increase of p27 kip1 expression by glomerular cells. This is in line with IL-10-induced B cell proliferation, which has been also reported to be mediated by decreased p27 kip1 (41). Therefore, one might expect that lowering p27 kip1 levels via neutralization of any one of the mesangial growth factors will result in amelioration of the disease.…”
Section: Discussionsupporting
confidence: 74%
“…We show that inhibition of IL-10 results in the increase of p27 kip1 expression by glomerular cells. This is in line with IL-10-induced B cell proliferation, which has been also reported to be mediated by decreased p27 kip1 (41). Therefore, one might expect that lowering p27 kip1 levels via neutralization of any one of the mesangial growth factors will result in amelioration of the disease.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have confirmed that p18 and p27 were involved in regulating different steps of B proliferation. Whereas p27 was thought to regulate cell cycle entry by forming a ternary complex with CDKs and cyclins, p18 was directly involved in induction of the G 1 cell cycle arrest by blocking the association of CDK4 and CDK6 with cyclin D (44). Interestingly, our data demonstrated that the mRNA level of p27, but not of p21 or p18, was up-regulated by 1,25(OH) 2 D 3 in activated human B cells.…”
Section: Discussionmentioning
confidence: 59%
“…Other CDK inhibitors have been shown to play an essential role in B cell responses. In this regard, p18 has been shown to be required for B cells to terminate proliferation and differentiate into functional plasma cells (38,43,44). Previous studies have confirmed that p18 and p27 were involved in regulating different steps of B proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Expression of p18 INK4C was reduced in poorly differentiated HCCs compared with levels in welland moderately differentiated HCCs, supporting the finding in previous reports that p18 INK4C accumulates at high levels in terminally differentiated cells. 22,42,43 However, our studies have not yet clarified whether the loss of p18 INK4C in HCC promotes or inhibits differentiation. These data suggest that decreased expression of p18 INK4C may play a role in the regulation of tumor differentiation as well as in the malignant transformation leading to HCC.…”
Section: Discussionmentioning
confidence: 87%